Niektóre aspekty przetwarzania obrazów wizualnych - Młodkowski, Jan (Acta Universitatis Lodziensis. Folia Psychologica, 2007)
Image is a fundamental concept for the subject being presented. The word “image” has especially multiple meanings. This paper contains some connotations of the notion of image with common knowledge, philosophy, physics, physiology and psychology. As the general conclusion coming from the presented review is the approval of the conception of image as a contemporary mentality paradigm. Philosophers actually tested if the world without the image as a constructional element is possible and how it could look like, and if the image is possible to exist without its object. In the cognitive psychology image processing is interpreted depending on the position regarding the number of existing codes. This paper refers to the author’s opinion that content processing depends on the form, vocabulary and alphabet that are used to express this content. The specificity of visual image processing is characterized by multidimensionality, adaptivity, intermodality and elasticity. These notions are explained in the paper.